(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
Materials, in general,play a big part in the teaching and learning processes of language acquisition. According to Richards (2001), "the majority of the language input that students receive and the language practice that takes place in the classroom is typically based on instructional materials" (p. 251). Global respect for the discipline of materials development as a scholarly area of study has grown in recent years. Materials development is "both a field of study and a practical undertaking," according to Tomlinson (2001). Its subject of study is the ideas and practices of creating, implementing, and assessing language learning resources (p. 66). This article discusses principles that should influence the design of materials as well as useful recommendations to keep in mind when teachers produce their own teaching materials.